Prospective Study of Breath-Holding Spells - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The natural history of severe breath-holding spells (BHS) was studied prospectively in 95 children (48 boys, 47 girls) referred for neurologic consultation at Children's Medical Center, Hartford, CT.